Developing a safety heatmap of uncontrolled intersections using both conflict probability and severity. (April 2018) - Ma, Yingying; Qin, Xiaoran; Grembek, Offer; Chen, Zhiwei
Highlights: Accident-data-free safety assessment method of uncontrolled intersection. Safety level index system to compare different uncontrolled intersections and schemes. Dangerous position management of intersection. Safety heatmap reflecting safety problems. Abstract: This paper presents a method to assess the safety of uncontrolled intersections considering two major properties of traffic conflicts—conflict probability and severity. This method assesses both the safety level of the entire intersection in addition to the distribution of safety within it. Intersections are modeled by a two-dimensional Cartesian coordinate system and the internal space of intersections is divided into cells. First, the vehicle movement characteristics of an uncontrolled intersection are modeled. Second, the conflict probability of each cell within the intersection is estimated considering the approaching probability and lateral migration probability of vehicles. The quantification of conflict severity is based on kinetic energy loss of potential crashes. Cluster analysis is used to combine conflict probability and severity to model the safety assessment of each cell. Third, the application of the method is discussed, and an overall safety index of intersections is proposed which considers weighted safety level and relative value of areas of different safety levels. Finally, a case study, which includes three different designs, is presented along with safety heatmaps to demonstrate the results. The results not only demonstrate the validity of the model, but also indicate that the proposed method can be applied to: i) safety evaluation of build-up intersections; ii) dangerous position management within an intersection; iii) safety assessment of designed intersections, and iv) safety level comparison among different intersections or various designs for a single intersection. Using this method, engineers and planners can better evaluate and improve the safety of existing or future uncontrolled intersections.